Estimation of Conditional Weighted Expected Shortfall under Adjusted Extreme Quantile Autoregression - Kithinji, Martin M.; Mwita, Peter N.; Kube, Ananda O. (Scientific Research Publishing Inc., 2021)
In this paper, we present an estimator that improves the well-calibrated coherent risk measure: expected shortfall by restructuring its functional form to incorporate dynamic weights on extreme conditional quantiles used in its definition. Adjusted Extreme Quantile Autoregression will is used in estimating intermediary location measures. Consistency and coherence of the estimator are also proved. The resulting estimator was found to be less conservative compared to the expected shortfall.
Keywords: Exreme Quantile Autoregression; Expected Shortfall; Value at Risk; Coherence; Risk Measurement